Effect of a Supportive Educational Program on Stress in Women with Endometrial Cancer - L Neisani Samani; AF Hoseini; M Modares Gilani; S Niroomand (Iran University of Medical Sciences, 2018)
Abstract Background & Aims: Endometrial cancer is the most common cancer of the female reproductive organs. Although widespread advances in the treatment of cancer has led to an increase in  patients' longevity, the cancer diagnosis and subsequently invasive procedures such as surgery, radiation therapy and chemotherapy often result in unpleasant complications in their life. The aim of this study is to determine the effect of a supportive educational program on stress in women with endometrial cancer. Material & Methods: In this interventional study which has been done in 2014, 140 women with endometrial cancer were randomly selected from Imam Khomeini Hospital Complex in Tehran. The intervention was a supportive educational program conducted in 3 sessions in the intervention group. The control group received routine care. Data were collected by the demographic form and the Hari's stress Inventory. The SPSS software version 16 and the t test, Chi-square and repeated measure analysis of variance were used to analyze the data. The level of significance was considered 0.05. Results: The stress mean score after the intervention, one month and two months later was significantly less than before the intervention(P<0.001). Conclusion: The study demonstrated that the supportive educational program was effective in reducing stress in women with endometrial cancer. It is suggested that the content of the program be provided to the patients in writing, such as pamphlets, bulletins, or via the Internet.